2020
DOI: 10.4081/cp.2020.1281
|View full text |Cite
|
Sign up to set email alerts
|

Success of Dental Implant Osseointegration in a Florid Cemento-Osseous Dysplasia: A Case Report with 8-Year Follow-Up

Abstract: Florid cemento-osseous dysplasia (FCOD) is a rare benign fibro-osseous lesion which affects multiple quadrants and predominantly the mandible. This case report presents a successful implant placement with 8-year of follow-up in a 44-yearold woman asking for a fixed restoration in mandibular right posterior edentulous area. Radiographic images showed lobular, irregularly shaped radiopacities and radiolucencies almost symmetrically observed in the premolar-molar area of the right and left regions of the mandible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…This was acheived by prescribing prophylactic antibiotic (amoxicillin/clavulanic acid 500 mg/125 mg) 1 h before surgery and chlorhexidine mouthwash preoperatively and postoperatively, by ensuring sterile environment during the procedure, minimizing periosteal reflection, making the procedure as short as possible, and avoiding overheating of the bone using cool sterile saline and sharp drills. No complications have occured after an 8-year follow-up (12).…”
Section: Shin Et Al Reported a Case Of Chronic Osteomyelitis Induced By The Placement Of Dental Implants On Codmentioning
confidence: 80%
“…This was acheived by prescribing prophylactic antibiotic (amoxicillin/clavulanic acid 500 mg/125 mg) 1 h before surgery and chlorhexidine mouthwash preoperatively and postoperatively, by ensuring sterile environment during the procedure, minimizing periosteal reflection, making the procedure as short as possible, and avoiding overheating of the bone using cool sterile saline and sharp drills. No complications have occured after an 8-year follow-up (12).…”
Section: Shin Et Al Reported a Case Of Chronic Osteomyelitis Induced By The Placement Of Dental Implants On Codmentioning
confidence: 80%
“…This was achieved by prescribing prophylactic antibiotic (amoxicillin/clavulanic acid 500 mg/125 mg) 1 h before surgery and chlorhexidine mouthwash preoperatively and postoperatively, by ensuring sterile environment during the procedure, minimizing periosteal reflection, making the procedure as short as possible, and avoiding overheating of the bone using cool sterile saline and sharp drills. No complications have occurred after an 8‐year follow‐up 12 …”
Section: Discussionmentioning
confidence: 92%
“…In 6 publications dealing with 6 cases, the implants were placed within or outside the lesion; [11,12,15,[17][18][19] only 3 cases among the 6 described were successfully integrated. [12,18,19] Gerlach et al [15] described implant failures in a FLCOD, but the mandible was also affected by a cemento-ossifying fibroma (COF).…”
Section: Discussionmentioning
confidence: 99%
“…In 6 publications dealing with 6 cases, the implants were placed within or outside the lesion; [11,12,15,[17][18][19] only 3 cases among the 6 described were successfully integrated. [12,18,19] Gerlach et al [15] described implant failures in a FLCOD, but the mandible was also affected by a cemento-ossifying fibroma (COF). Oliveira et al, [17] as well as Shin et al, [11] have also reported cases of implants failures in FLCOD manifested by the loose implant, swelling, and pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation